Shu ju ke xue zhong de shi yong tong ji xue = Practical statistics for data scientists - Bruce, Peter C., 1953-; Bruce, Andrew, 1958-; Gedeck, Peter (O'Reilly Media ; Ren min you dian chu ban she, 2021)
Detailed summary in vernacular field.